Trans*-Subjectivity: Exploring Research Positionality in the Field - Whitley, Cameron T. (Qualitative Sociology Review, 2015)
The focus on trans*1 individuals as researcher subjects often problematizes trans* identity, limiting the possibility for trans* individuals to create and co-create bodies of knowledge. Drawing on three years of participatory research in the animal production industry, I discuss the implications of my subjectivity as a trans* man in this particular setting and in my research more broadly. Beyond being a self-reflexive exercise, this study seeks to make a number of theoretical and empirical contributions. First, feminist literature discussing one’s subjectivity has largely focused on the dialectical existence between men and women, with little room for trans* or gender diverse perspectives. Further, studies that have acknowledged trans* identity have done so in relation to trans* persons as research subjects, with no recognition of their positionality or the possibility of the trans* researcher. This study seeks to change these paradigms by extending current feminist research frameworks on subjectivity to include greater gender diversity.